2018
DOI: 10.1177/0898756418814010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Passive Immunization by Anti-Gingipain IgY on the Oral Health of Cats Fed Kibble Diets

Abstract: Porphyromonas gulae is one of the key microorganisms in biofilm dysbiosis that leads to periodontal disease, a prevalent disease in cats. Gingipains are proteases secreted that promote the disruption of cell adhesion and the differentiation of osteoclasts. The use of anti-gingipain immunoglobulin Y (IgY-GP) has emerged as a promising alternative to conventional prevention and treatment methods. The aim of this study was to evaluate the efficacy of IgY-GP on different parameters related to oral health in cats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…After 40 days of a diet enriched with specific IgY (around 213 mg of IgY/cat/day), the analyzed parameters such as plaque formation, dental calculus, gingivitis index, and percentage of Porphyromonas gingivalis of the oral cavity were evaluated. The plaque index was reduced when compared to the control group ( 325 ).…”
Section: Porphyromonas Gingivalismentioning
confidence: 77%
“…After 40 days of a diet enriched with specific IgY (around 213 mg of IgY/cat/day), the analyzed parameters such as plaque formation, dental calculus, gingivitis index, and percentage of Porphyromonas gingivalis of the oral cavity were evaluated. The plaque index was reduced when compared to the control group ( 325 ).…”
Section: Porphyromonas Gingivalismentioning
confidence: 77%
“…In addition, in vivo trials are introduced to investigate the therapeutic effects of IgY. For instance, Oba and colleagues demonstrated that the consumption of specific IgY against P. gingivalis gingipain reduces the accumulation of subgingival dental plaque in cats [ 35 ]. Also, treatment with IgY from hens immunized with whole F. nucleatum cells results in a marked decrease in alveolar bone loss after F. nucleatum infection in a mouse model [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…By blocking the effect of gingipains it avoids the disruption of cell adhesion and therefore, prevent the formation of periodontal pocket and consequently the progression of periodontal disease [23,24]. In cats, the consumption this additive on the diet coat (4g/kg of diet) was able to reduce dental plaque [14]. In dogs, 35mg/kg of body weight once a day and 17.5mg/kg of body weight twice a day reduced significantly the dental calculus and gingivitis [13].…”
Section: Nutrition and Food Science International Journalmentioning
confidence: 99%
“…Blocking the effect of gingipain this additive prevents the formation of periodontal pocket and consequently the progression of periodontal disease. Positive results with the use of IgY-GP in the oral health of dogs and cats have been reported, reducing dental plaque in cats and dental calculus and gingivitis in dogs [13,14]. Omega-3 can control the production of inflammatory compounds aiding in cases where periodontal disease already causes inflammation and pain [15].…”
Section: Introductionmentioning
confidence: 99%